Investigative journalism in Malaysia: the battle between outside and inside newsroom challenges - Ismail, Adibah; Ahmad, Mohd Khairie; Mustaffa, Che Su (EDP Sciences, 2017)
Investigative journalism originated in Western countries but the practice has spread throughout the world, including countries with different political and media environment.Current literature is dominated by Western perspectives, focusing mainly on the developed countries viewpoint.This study is exploring a controlled media environment, focusing on Eastern developing country. This research explores media practitioners’ perception on challenges of practicing investigative journalism in Malaysia.In-depth interviews were used in this research.A total of 16 informants were interviewed.Data was examined using thematic analysis.It was found that Malaysian media practitioners acknowledged six outside challenges and eight inside the newsroom challenges.The study concludes that challenges in controlled media environment revolve around press freedom issue and inside the newsroom struggles due to different editorial orientation on the value of investigative journalism.